Landasan Puritanisme Sosial Agama Pesantren: Pemikiran Kiai Sahal Mahfudz - Ahmad Ali Riyadi (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2016)
This study to new concept discussed of pesantren scientific to get contribution in Islamic education and a new varian model of pesantren to give alternative solution of it social changes. This method of research make use of literature of primery and secondary investigation, and it analysis method using fenomenology approach with ethnography method. This result of research is revitalitation of pesantren scientific meaning with reform to understand of religion considered as part of social chages movement with religion values. The pesantren scientific revitalitation was involving a big impact of social development in pesantren social eround. Revitalitation of pesantren scientific involved by implication of it movement a new work spirit in pesantren community and direct with deceive of pesantren area based by kitab kuning study as teks emansipatory base.